The Interplay between Logistic Services and Customer Satisfaction in e-services: A Case Study - Eltigani, Mohammed; Abdullah M. Al-Ansi (Graduate School Universitas Brawijaya, 2026)
Objective: The aim of this case study is to investigate the role of logistic services in customer satisfaction. The logistics services were investigated under three dimensions including delivery time, product availability and technical issues while customer satisfaction was investigated in four dimensions including product quality, communication, order accuracy and product price. Design/Methods/Approach: The data was collected through online survey of e-shoppers from Lulu Hypermarket in Oman to fill the questionnaire. Also, interviews with some e-shoppers were conducted to understand their perspectives and satisfaction regarding e-services. The sample consists of 100 individuals who participated in this case study voluntarily. Data was analyzed using SPSS through descriptive statistics, correlation and regression analysis. Findings: The level of both logistic services and customer satisfaction in Lulu Hypermarket was high based on the means of the case study participants. Furthermore, the results illustrated that logistic services dimensions have positive and significant influence on customer satisfaction with (0.586, 0.214 and 0.109) respectively. Originality/Value: This case study highlights the role and importance of appropriate logistics in enhancing customer satisfaction especially in online shopping. Practical/Policy implication: By understanding the relationship between logistics services and customer satisfaction, the management at Lulu can identify opportunities for improvement and devise effective strategies to enhance the overall shopping experience for their customers. Keywords: Customer Satisfaction; Case Study; E-Services; Logistic Services; Lulu Hypermarket JEL Classification: L81; M31; L87